Attitudes to Palliative Care in Patients With Neck-of-Femur Fracture—A Multicenter Survey. (16th April 2020) - Harries, Luke; Moore, Andrew; Kendall, Clare; Stanger, Sophie; Stringfellow, Thomas D.; Davies, Andrew; Kelly, Mike
Introduction: The mortality of patients with neck-of-femur (NOF) fractures remains high, with increasing recognition of a subgroup of patients with predictable mortality. The role of palliative care in this group is poorly understood and underdeveloped. This research aims to investigate current clinician attitudes toward palliative care for patients with NOF fracture, and explore processes in place for early identification for patients nearing the end of life. Materials and Methods: An online survey was constructed with reference to National Institute for Health and Clinical Excellence end-of-life guidelines (CG13) and distributed to multidisciplinary teams involved in the care of NOF fracture patients in 4 hospitals of contrasting size and location in the United Kingdom. Results: Forty health-care professionals with a broad range of seniority and roles responded. The palliative care team was felt to have several potential roles in the care of NOF fracture patients, but there was difference of opinion between specialties about what these were. A number of barriers to palliative referral were identified, including stigma and active surgical management. The majority (75%) felt that all NOF fracture patients should have a discussion about ceiling of care, with difference of opinion about who should do so, and when. Discussion: As the elderly population has grown, so too has the volume of NOF fracture patients. It is increasingly important to identify and escalate patients who have poor prognosis following hip fracture and ensure they benefit from palliative care where appropriate. This survey demonstrates a barrier to addressing the care of these patients and a lack of consensus on identification and referral to appropriate palliative care planning. Conclusions: There should be close communication between specialties with regard to requirements for palliative care in NOF fracture patients, with ongoing education and clear local and national guidance to ensure they receive the right care at the right time.